Pharmaceutical Innovation and Drug Policy: The Case of the 1984 Hatch-Waxman Act - Benjamin M. Blau; Joshua Lyman; Jason M. Smith; Ryan J. Whitby (PLoS ONE, 2026)
This paper examines the effect of the 1984 Hatch-Waxman Act and its 2003 amendment – the Medicare Prescription Drug, Improvement, and Modernization Act – on the level of innovation in pharmaceutical firms. In part, the purpose of these policies was to balance the exclusivity rights of pioneer drug manufacturers with generic drug competition, which would allow for more consumer affordability. Using difference-in-difference regression analysis, we analyze how, relative to innovation in other industries, pharmaceutical innovation changes surrounding the implementation of the two laws. Results from several difference-in-difference tests show that, relative to non-pharmaceutical firms, research and development (R&D) in pharmaceutical firms markedly increased during the post-Hatch-Waxman period. We do not find, however, that the 2003 amendment directly influenced pharmaceutical innovation. If anything, the latter policy was associated with a reduction in innovation. These findings seem to suggest that the level of pharmaceutical innovation is highly sensitive to changes in policy that might change the incentives for firms to innovate.